Analisa kasus kista ovarium di Rumah Sakit Umum Pusat (RSUP) Haji Adam Malik Medan periode I Januari 2010 - 31 Desember 2012 - Dona Wirniaty; M. Fidel G Siregar; Rushakim Lubis; Henry Salim Siregar; Iman Helmi Effendi; Johny Marpaung (Majalah Kedokteran Nusantara The Journal Of Medical School, 2015)
Introduction : Ovarían cysts are cystic neoplasms derived from ovarian tissue, can be benign or malignant. Characteristics ofovarian cysts is importantto be known, such as body mass index and risk ofmaligriancy index. Not only to be able to assess risk factors but also early detection prompt treatment to prevent progression to ovarian cancer.Methods : This is a descriptive study, conducted in Department of Obstetrics and Gynecology Hospital, Adam Malik Medan Medical records from all patients who will undergo elective surgery for ovarian cysts from January Pt 2010 to December 31th 2012 was collected. Data was analyzed descriptively and analytically with chi square by level of significance in this study was p<O.05.Results : There were 327 patients with ovarian cyst undergoing elective surgery in H. Adam Malik Hospital from January 2010  to December 201 2 but only I 99 were included in the study. Majority of patients with malignant ovarian cysts aged 51 years old (38.9%), number of pañty 2-5 (41 .7%), menarche at 1 3-16 years old (72.2%), BMI normoweight (44, 4%), levels of CA 125> 35 U/ml (95.8%), and the RMI > 250 (88.9%). Majority of patients with benign ovarian cysts aged 31-40 year olds (28.3%), parity 2-5 (46.5%), menarche at 13-16 years old (85.4%), BMI obese (44.9%), CA 125 levels similar, and RML 250 (63.8%).  The most common ovarian cyst is malignant adenocarcinoma (72 patients, 36.2%). This study showed that BMI (p=O.OO8) and RMI (jsO.OO1 ) are associated with ovarian cyst. Conclusion: This study showed that there is association of body mass index and risk of malignancy index with ovarian cysts.  Need further research with larger population samples. Keywords : Ovarían cysts; Body Mass Index; Risk of Malignancy index